Apocynin: Chemical and biophysical properties of a NADPH oxidase inhibitor - Petrônio, Maicon S. [UNESP]; Zeraik, Maria Luiza [UNESP]; Da Fonseca, Luiz Marcos [UNESP]; Ximenes, Valdecir F. [UNESP] (MDPI, 2013)
Apocynin is the most employed inhibitor of NADPH oxidase (NOX), a multienzymatic complex capable of catalyzing the one-electron reduction of molecular oxygen to the superoxide anion. Despite controversies about its selectivity, apocynin has been used as one of the most promising drugs in experimental models of inflammatory and neurodegenerative diseases. Here, we aimed to study the chemical and biophysical properties of apocynin. The oxidation potential was determined by cyclic voltammetry (Epa = 0.76V), the hydrophobicity index was calculated (logP = 0.83) and the molar absorption coefficient was determined (ε275nm = 1.1 × 104 M-1 cm-1). Apocynin was a weak free radical scavenger (as measured using the DPPH, peroxyl radical and nitric oxide assays) when compared to protocatechuic acid, used here as a reference antioxidant. On the other hand, apocynin was more effective than protocatechuic acid as scavenger of the non-radical species hypochlorous acid. Apocynin reacted promptly with the non-radical reactive species H2O2 only in the presence of peroxidase. This finding is relevant, since it represents a new pathway for depleting H2O2 in cellular experimental models, besides the direct inhibition of NADPH oxidase. This could be relevant for its application as an inhibitor of NOX4, since this isoform produces H 2O2 and not superoxide anion. The binding parameters calculated by fluorescence quenching showed that apocynin binds to human serum albumin (HSA) with a binding affinity of 2.19 × 104 M -1. The association did not alter the secondary and tertiary structure of HSA, as verified by synchronous fluorescence and circular dichroism. The displacement of fluorescent probes suggested that apocynin binds to site I and site II of HSA. Considering the current biomedical applications of this phytochemical, the dissemination of these chemical and biophysical properties can be very helpful for scientists and physicians interested in the use of apocynin.
Keywords: Albumin; Apocynin; Binding constant; Hydrogen peroxide; NADPH oxidase; acetophenone derivative; apocynin; enzyme inhibitor; hydrogen peroxide; hypochlorous acid; reduced nicotinamide adenine dinucleotide phosphate oxidase; scavenger; chemical phenomena; chemistry; drug antagonism; kinetics; oxidation reduction reaction; pH; Acetophenones; Enzyme Inhibitors; Free Radical Scavengers; Hydrogen Peroxide; Hydrogen-Ion Concentration; Hydrophobic and Hydrophilic Interactions; Hypochlorous Acid; Kinetics; NADPH Oxidase; Oxidation-Reduction